Połączenie sztucznej inteligencji i tokenów NFT – nowe wyzwania dla rynku sztuki? - Włodzimierz Szpringer (Studia i Materiały)
Purpose: The article aims to identify the challenges for the art market resulting from the use of generative artificial intelligence (GenAI) and in particular the interdependence between GenAI and NFT tokens.